Catalyst : celebrating 25 years Fanshawe College Fine Art. - Fanshawe College Fine Art, London (London : Regional Art Gallery, 1994)
Binks, Geri ; Bobier, David ; Bondarchuk, Karen ; Brain, John ; Burk, Noeline L. ; Clarke, Nancy ; Confort, Ruth ; Cowle, Ron ; Coyle, Janice ; etc.
Catalyst : celebrating 25 years Fanshawe College Fine Art, Regional Art Gallery & Historical Museums, London, Ontario, February 19 - May 1, 1994
boek